Creating a Model-Based Learning Environment in BIM Education through Case Studies - Semih Göksel Yıldırım (Journal of Architectural Sciences and Applications, 2024)
As demand in the construction industry continues to rise globally, universities have shown an increased interest in Building Information Modeling (BIM) education, leading to accelerated curriculum development studies. Previous research has identified several challenges associated with creating new BIM course curricula. Notably, the instructor's competence in delivering the practical components of the course and developing assignment content are significant issues. The development of case studies aims to enhance the BIM proficiency of course instructors and to generate course materials suitable for practical application. This paper outlines the design of course content for BIM curriculum development through the use of case studies. Case studies from various building programs are evaluated and compared based on their BIM maturity levels. The resulting course materials are implemented in a graduate course offered each year and assessed through student surveys. The intricate nature of BIM is explained within a model-based learning environment. By analyzing the learning environment using data gathered from student surveys, this study aims to provide insights for future improvements.